Balancing China: Indo-US relations and convergence of their interests in the Indo-Pacific. (2nd January 2021) - Lobo, J. Susanna
ABSTRACT: The Indo-Pacific has emerged as an important region in international politics where the major powers are deeply engaged in reshaping the security architecture. Over the last few years, India and China have drawn their policies by employing competitive strategies that strengthen as well as neutralise their respective power positions in the Indian Ocean Region, particularly in South Asia and the South China Sea. China's "String of Pearls" strategy and the "Belt and Road Initiative" undermine India's influence in the Indian Ocean Region, where the changing geo-economic and geostrategic imperatives pose threat to its interests. This mounts pressure on New Delhi to respond by pursuing counter-strategies to secure its interests in the Indo-Pacific region. The article further explains how India and the United States' interests are converging against an assertive China in the Indo-Pacific and how the two states' security and maritime collaborations are balancing their common rival by maintaining a favourable status quo in the region.